2016
DOI: 10.1177/0887403416635248
|View full text |Cite
|
Sign up to set email alerts
|

Sentencing on the Evidence

Abstract: The type and quantity of evidence in a case is a critical factor for deciding guilt but should have little or no influence on the sentencing determinations of judges post conviction; this is because case evidence goes to guilt decisions by triers of fact, whereas sentences are imposed upon those already convicted. This study examines the effects of evidentiary type and the total quantity of physical evidence in a case on length of custodial sentence. The results demonstrate that violent felony cases with foren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Second, the USSC data provide details on several important variables that capture both legally relevant and extra-legal factors that can influence sentencing decisions. Still, there are potentially important variables such as the type of attorney (i.e., private vs. public defender) an individual had (Hartley et al, 2010), the presence of physical evidence Nir & Griffiths, 2018;Spears & Spohn, 1997), and details of the victim characteristics (Spohn & Spears, 1996) that could influence sentence decisions, and the commission could assist in a better understanding of the determinants of sentences by adding these variables to its current data sets. Third, the current study focused on decisions at the final sentencing stages (i.e., sentence length and guideline departure).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the USSC data provide details on several important variables that capture both legally relevant and extra-legal factors that can influence sentencing decisions. Still, there are potentially important variables such as the type of attorney (i.e., private vs. public defender) an individual had (Hartley et al, 2010), the presence of physical evidence Nir & Griffiths, 2018;Spears & Spohn, 1997), and details of the victim characteristics (Spohn & Spears, 1996) that could influence sentence decisions, and the commission could assist in a better understanding of the determinants of sentences by adding these variables to its current data sets. Third, the current study focused on decisions at the final sentencing stages (i.e., sentence length and guideline departure).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the gatekeeping and political power of the police, however, information about the type and amount of influence that officers have over case processing remains limited. Research shows that the strength and type of evidence gathered can shape case outcomes such as prosecutorial charging decisions (Lee & Testa, 2020;Spears & Spohn, 1997), plea bargaining outcomes (Albonetti, 1990;Jacoby & Ratledge, 2016), and sentences (Nir & Griffiths, 2018). Focusing on the frequency of interaction between police officers and court actors, Sloan and Miller (1990) found that being a "repeat player" police officer did not impact charge reductions in felony drug cases.…”
Section: Police Influence In the Courtroommentioning
confidence: 99%